Вибір оптимальної структури системи технічного обслуговування та ремонту розподільної мережі 6–35 кВ з повітряними лініями електропередачі - Ілюхін, М.О. (Технічна електродинаміка, 2012)
Proven that for power grids 6-35 kV, as an object of diagnosticating, most effective is the mixed method of construction of the combined system of diagnosticating, when facilities of automatic control of isolation dispose on substation, fixing of parameters of malfunction for a distance-finding to the place damages which form group in separate blocks, central part of the combined system of diagnosticating is autonomous. Information about the technical state is passed on the channels of teleautomatics and radio contact on controller's point, where made decision about the further use of object. Model which represents office hours built as a count, her analysis allows to find the optimization method of placing of apparatus of diagnosticating and rational betweenness by the volume of the controlled operations which are executed by hand, and volume of the automated operations.